Evaluasi Perancangan Kolom Beton Bertulang dengan Metode Elemen Hingga - Bayzoni Bayzoni; Laksmi Irianti; Vera Chania Putri (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
The design of a column is performed particularly to prevent any excessive deformation when it is used to support working load, and still have sufficient safety and reserve strength to withstand the load and stress without experiencing the collapse. The process of design or analysis generally begins with a compliant againt flexure, and the other requirements such as shear, crack, anchorage length were so that all requirment satisfied. The aim of this research is to get the stress of reinforced concrete column using the finite element method, so that it can get an evaluation of the design of reinforced concrete columns by comparing the stress design with the stress obtained from the finite element method. The calculations result shown that the enlargement deflection in horizontal direction is greater than the value of the enlargement deflection in vertical direction, that cause of the influence of axial forced and bending moment. From the results of stress analysis in steel and concrete by using the finite element method has a value less than fy and f'c used in the design. This shows the reinforced concrete column can withstand a greater load than the load value which was assumed the column on the balance condition